The productivity-wage gap and the current account balance : examining causality - Cain, Donneil ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Uses an unbalanced annual panel data for Barbados 1985-2001; Jamaica 1972-2005; and Trinidad 1985-2001; to determine whether there indeed exists a causal relationship between the wage-productivity gap and the current account.